KHWAREZMIAN AND MONGOL CONQUESTS OF THE SOUTH CAUCASUS IN FOREIGN HISTORIOGRAPHY: IN THE CONTEXT OF D. BAYARSAIKHAN’S RESEARCH "THE MONGOLS AND THE ARMENIANS (1220-1335)" - Timohin, Dmitrij Mihajlovic (History, Archeology and Ethnography of the Caucasus, 2017)
The article deals with the analysis of foreign researches of Mongol and Khwarezmian conquests of the South Caucasus. The subject of study is one of the latest works on this problem – D. Bayarsaikhan’s monograph «The Mongols and the Armenians (1220-1335)». The author of the article details historiography and source study of the book under consideration, as well as those sections, which present the description of Mongol and Khwarezmian invasion of the territory of the South Caucasus and the consequences of these conquests. Much attention is given to the section of D.Bayarsaikhan’s monograph describing the political structure of the South Caucasus at the beginning of the 13 th century and a number of earlier events. The author of the article also analyzes D. Bayarsaikhan’s position on a number of debatable problems concerning political history of the South Caucasus in the first half of the 13 th century. The author focuses on the idea of political history of the South Caucasus in the first half of the 13 th century that readers may get after their acquaintance with D. Bayarsaikhan’s book «The Mongols and the Armenians (1220-1335)». The fact that the monograph of D. Bayarsaikhan has not been translated into Russian yet and is not well known to specialists in Russia gives special significance to this article. To date, there are not many special studies on this problem in Russian science, therefore it is extremely important to study foreign experience in this field